Association between gingival tissue biotype and different facial phenotypes - Mousa Assiri; Sami Shafik; Ahmed Tawfig (Elsevier, 2019)
Objective: This study was conducted to investigate the association between gingival tissue biotypes and different facial phenotypes. Method: This was a cross-sectional study conducted in the dental clinics of Riyadh Elm University, Riyadh, Saudi Arabia. Gingival tissue biotypes were assessed and facial measurements recorded for 80 subjects who met the inclusion criteria. Data are presented as numbers (percentages) for all categorical variables and mean ± standard deviation plus median (interquartile range) for all continuous variables. Both descriptive and inferential statistics were analyzed and a P-value ≤ 0.05 was accepted as significant for all statistical tests. Results: The age range of the participants was 21-40 years (mean 28.8 ± 04.3), and the majority were males (65.0%). The thin gingival tissue biotype was found in 39 subjects (48.8%) while the thick gingival biotype was present in 41 subjects (51.2%). The majority of patients were mesoprosopic (41.2%), followed by those who were leptoprosopic (37.5%) and euryprosopic (21.3%). The thick gingival tissue biotype was more prevalent in 21-30-year-old patients. The mesoprosopic facial phenotype was significantly associated with presence of the thin gingival tissue biotype (odds ratio = 3.600, p = 0.049). Conclusions: It was found that the mesoprosopic facial phenotype was more likely to exhibit the thin gingival tissue biotype. The mesoprosopic facial phenotype was the most common facial phenotype of the subjects. The thick gingival tissue biotype was more prevalent in younger people. Keywords: Gingival tissue biotype, Facial morphology phenotypes, Thin, Thick, Mesoprosopic, Association